Fugitive telemetry - Wells, Martha (The Murderbot diaries, 2021)
"When Murderbot discovers a dead body on Preservation Station, it knows it is going to have to assist station security to determine who the body is (was), how they were killed (that should be relatively straightforward, at least), and why (because apparently that matters to a lot of people-who knew?) Yes, the unthinkable is about to happen: Murderbot must voluntarily speak to humans! Again! A new standalone adventure in the New York Times-bestselling, Hugo and Nebula Award winning series!"--